Current Trends Overview on Malaysian Higher Education System towards Industry 4.0 - Maria, Meylinda; Shahbodin, Shahbodin; Che Pee, Naim (International Journal of Engineering and Technology, 2018)
Industrial revolution has taken its place globally with the term of Industry 4.0. Moreover, it triggers the new term of Education 4.0 as one of the impacts which came from the education sector. The aim of this study is to provide a view of the current trend in the industrial revolution â€“ Industry 4.0, Education 4.0, followed by the look on higher education system in Malaysia. Focused on the efforts made by the Malaysian government of higher education (MoHE), it is shown that Malaysia is aware on this current global issue and is preparing to implement Industry 4.0 and Education 4.0 to their current system.Â